Behavioral Changes on the Impact of Single Parent Women's Empowerment in Meeting Family Needs (Study on the Indonesian Association of Women with Disabilities Garut Regency) - Karwati, Lilis; Yuliana, Anna; Shaleha, Resha Resmawati (Journal of Cultural Analysis and Social Change, 2026)
Women with disabilities are single parents as the head of the family who bear the economic burden of the family so they need to be empowered to bring change through coaching and training in the field of entrepreneurship. The purpose of this study is to determine behavioral changes due to the empowerment of single parent women in meeting family needs with a descriptive method. Data collection through documentation techniques, observation and in-depth interviews with resource persons to understand complex phenomena Based on the results of research on behavioral changes of women with disabilities single parent the impact of change empowerment Having awareness of Interest, Evaluation, and Adoption of behavioral changes as an impact on single parent women there is an increase in being able to adapt to the reality of life and having personal resilience with the involvement of Role active, have commitment, control, and be ready to face challenges can improve knowledge and skills There is a change in mindset, namely a change that women have the potential to be developed so as to provide a change in independence that can have an impact on meeting family needs.